A new clade of archaic large-bodied predatory dinosaurs (Theropoda: Allosauroidea) that survived to the latest Mesozoic. - Benson, R; Carrano, M; Brusatte, S (2010)
Non-avian theropod dinosaurs attained large body sizes, monopolising terrestrial apex predator niches in the Jurassic-Cretaceous. From the Middle Jurassic onwards, Allosauroidea and Megalosauroidea comprised almost all large-bodied predators for 85 million years. Despite their enormous success, however, they are usually considered absent from terminal Cretaceous ecosystems, replaced by tyrannosaurids and abelisaurids. We demonstrate that the problematic allosauroids Aerosteon, Australovenator, Fukuiraptor and Neovenator form a previously unrecognised but ecologically diverse and globally distributed clade (Neovenatoridae, new clade) with the hitherto enigmatic theropods Chilantaisaurus, Megaraptor and the Maastrichtian Orkoraptor. This refutes the notion that allosauroid extinction pre-dated the end of the Mesozoic. Neovenatoridae includes a derived group (Megaraptora, new clade) that developed long, raptorial forelimbs, cursorial hind limbs, appendicular pneumaticity and small size, features acquired convergently in bird-line theropods. Neovenatorids thus occupied a 14-fold adult size range from 175 kg (Fukuiraptor) to approximately 2,500 kg (Chilantaisaurus). Recognition of this major allosauroid radiation has implications for Gondwanan paleobiogeography: The distribution of early Cretaceous allosauroids does not strongly support the vicariant hypothesis of southern dinosaur evolution or any particular continental breakup sequence or dispersal scenario. Instead, clades were nearly cosmopolitan in their early history, and later distributions are explained by sampling failure or local extinction.